University Students’ Perceptions of Duolingo as a Gamified Tool for English Vocabulary Learning - Novita Putri Ramadhani; Dzul Rachman; Khusnul Khatimah (Borneo Educational Journal (Borju), 2026)
This study examines university students' impressions of Duolingo as a gamified tool for improving English vocabulary acquisition. This study used a mixed-method methodology, integrating quantitative data from 58 first-semester students at Universitas Muhammadiyah Kalimantan Timur with qualitative insights derived from five interviews. The study seeks to examine Duolingo's impact on vocabulary acquisition, learner motivation, and autonomous learning. Findings suggest that students predominantly view Duolingo as stimulating and beneficial for vocabulary acquisition, facilitated by its interactive elements like points, streaks, and prompt feedback. Nonetheless, constraints were observed, including reliance on the internet, restricted classroom integration, and insufficient teacher engagement. Although Duolingo seems to promote motivation and autonomous learning, its effect on vocabulary acquisition is contingent upon context. These data indicate that Duolingo serves more effectively as an ancillary learning resource rather than a substitute for classroom education